Aiming for G7 Master Compliance through a Color Managed Workflow: Comparison of Compliance with Amplitude Modulated (AM) vs. Frequency Modulated (FM) Screening of Multicolor Digital Printing - Naik Dharavath, Haji (Journal of Graphic Engineering and Design, 2021)
The purpose of this research was to determine the influence of screening technologies (AM vs. FM) in the color reproduction aimed at the G7 master compliance. The quality of digital color printing is determined by these influential factors: screening method applied, type of printing process, ink (dry-toner or liquid-toner), printer resolution and the substrate (paper). For this research, only the color printing attributes such as the G7 colors hue and chroma, gray balance, and overall color deviations were analyzed to examine the significant differences that exist between the two screening technologies (AM vs. FM). These are the color attributes which are monitored and managed for quality accuracy during the printing. Printed colorimetry of each screening from the experiment was compared against G7 ColorSpace GRACoL 2013 (CGATS21-2-CRPC6) in CIE L* a* b* space using an IDEAlliance (Chromix/Hutch Color) Curve 4.2.4 application interface with an X-Rite spectrophotometer with an i1iO table. The measured data of each screening were run through this application (Curve 4.2.4). The data of each screening were analyzed by using the Verify Tool of the Curve 4.2.4 application to determine the pass/fail of G7 master compliance levels using G7 ColorSpace tolerances (G7 Grayscale, G7 Targeted, and G7 Colorspace). Analyzed data from the experiment revealed that the printed colorimetric values of each screening (G7 Grayscale, G7 Targeted, and G7 Colorspace) are in match (aligned) with the G7 master compliance levels (reference/target) colorimetric values (G7 Grayscale, G7 Targeted, and G7 Colorspace). Therefore, the press run was passed by the Curve 4 application for both screening technologies tested. Article history: Received (December 15, 2020); Revised (February 9, 2021); Accepted (February 25, 2021); Published online (June 1, 2021)